Analisis Biaya Produksi dalam Peningkatan Penjualan: (Studi Kasus Industri Kecil Sultan Bakery di Bandarjo Dusun II, Kec. Pasaman, Kab. Pasaman Barat) - Mardiana Mardiana; Yossi Eriawati; Novi Susanti (Universitas 45 Surabaya, 2025)
This study aims to analyze production costs in increasing sales in the Sultan Bakery small industry in Bandarjo Dusun II, Kec.Pasaman, Kab.Pasaman Barat. The main focus of the research includes the relationship between production costs and selling prices, the effectiveness of production cost management on profit margins and increased sales, and factors that influence production costs in the context of market competitiveness. This research used a qualitative method with a descriptive approach, where data were obtained through observation, in-depth interviews, and documentation studies. The results showed that efficiency in managing production costs has a significant influence on the ability of businesses to set competitive selling prices. The main factors that support this efficiency include raw material management, labor optimization, and overhead cost control. In addition, the selection of quality raw materials and effective labor management help maintain cost stability without compromising product quality. This strategy not only maintains customer loyalty but also increases the competitiveness of the business in the local market. The increase in sales achieved by Sultan Bakery is consistently supported by planned cost management, production scale efficiency, and the application of modern technology. This study concludes that production cost efficiency plays an important role in supporting profit margins, increasing sales, and strengthening the competitiveness of small businesses in the local market.